Lifelong Adaptation of Gastric Cell Proliferation and Mucosa Structure to Early Weaning-Induced Effects - Mesquita da Silva, Kethleen; Rattes, Isadora Campos; Pereira, Gizela Maria Agostini; Gama, Patrícia (Frontiers in Physiology, 2021)
The gastric mucosa is disturbed when breastfeeding is interrupted, and such early weanling (EW) condition affects permanently the differentiation of zymogenic cells. Currently, our aim was to evaluate the immediate and long-term effects of EW on gastric cell proliferation, considering the molecular markers for cell cycle, inflammation, and metaplasia. Overall, we investigated the lifelong adaptation of gastric growth. Wistar rats were divided into suckling-control (S) and EW groups and gastric samples were collected at 18, 30, and 60 days for morphology, RNA, and protein isolation. Inflammation and metaplasia were not identified, but we observed that EW promptly increased Ki-67-proliferative index (PI) and mucosa thickness (18 d). From 18 to 30 d, PI increased in S rats, whereas it was stable in EW animals, and such developmental change in S made its PI higher than in EW. At 60 d, the PI decreased in S, making the indices similar between groups. Spatially, during development, proliferative cells spread along the gland, whereas in adults, they concentrate at isthmus-neck area. EW pushed dividing cells to this compartment (18 d), increased PI at gland base (60 d), but it did not interfere in expression of cell cycle molecules. At 18 d, EW reduced Tgfβ2, Tgfβ3 and Tgfbr2 and TβRII and p27 levels, that might regulate the proliferative increase at this age. We demonstrated that gastric cell proliferation is immediately upregulated by EW, corroborating previous results, but for the first time we showed that such increased PI is stable during growth and aging. We suggest that suckling and early weaning might use TGFβs and p27 to trigger different proliferative profiles during life course.